Identificación de un compuesto alelopático de Baccharis boliviensis (Asteraceae) y su efecto en la germinación de Trichocereus pasacana (Cactaceae) - Cazón, Ada (Universidad de Costa Rica, 2000)
The genus Baccharis has a wide distribution in Northwestern arid regions of Argentina. Studies carried out on the spatial distribution of T. pasacana in relation to the available space, show that although beneath B. boliviensis canopy, cacti seeds are abundant, no adult plants are found growing in association to that species in spite of the requirement of a nurse plant for a successfull cacti establishment. Hexane, chloroforrn and ethyl acetate extracts from B. boliviensis folliage inhibited T. pasacana gennination completely.The bioassays were carried out in a germination chamber following a random design, with four replicates by treatment. The chloroforrn extract was the most effective solvent for extracting the phytotoxic material from the aqueous extracts. T he ferrulic acid structure was deterrnined by !3C NMR, lHNMR spectra and TLC on silica gel.